A benign juvenile environment reduces the strength of antagonistic pleiotropy and genetic variation in the rate of senescence. (19th December 2015) - Kim, Sin‐Yeon; Metcalfe, Neil B.; Velando, Alberto
Summary: The environment can play an important role in the evolution of senescence because the optimal allocation between somatic maintenance and reproduction depends on external factors influencing life expectancy. The aims of this study were to experimentally test whether environmental conditions during early life can shape senescence schedules, and if so, to examine whether variation among individuals or genotypes with respect to the degree of ageing differs across environments. We tested life‐history plasticity and quantified genetic effects on the pattern of senescence across different environments within a reaction norm framework by using an experiment on the three‐spined stickleback ( Gasterosteus aculeatus, Linnaeus) in which F1 families originating from a wild annual population experienced different temperature regimes. Male sticklebacks that had experienced a more benign environment earlier in life subsequently reduced their investment in carotenoid‐based sexual signals early in the breeding season, and consequently senesced at a slower rate later in the season, compared to those that had developed under harsher conditions. This plasticity of ageing was genetically determined. Both antagonistic pleiotropy and genetic variation in the rate of senescence were evident only in the individuals raised in the harsher environment. The experimental demonstration of genotype‐by‐environment interactions influencing the rate of reproductive senescence provides interesting insights into the role of the environment in the evolution of life histories. The results suggest that benign conditions weaken the scope for senescence to evolve and that the dependence on the environment may maintain genetic variation under selection. Abstract : The authors pose an interesting question of whether environmental conditions can shape senescence schedules, and test this in an experimental study of a short‐lived vertebrate species. They demonstrate genotype‐by‐environment interactions shaping the rate of senescence. The results suggest that benign conditions weaken the scope for senescence to evolve.